Optimizing canopy-spacing configuration increases soybean yield under high planting density - Ruidong Li; Cailong Xu; Zongsheng Wu; Yifan Xu; Shi Sun; Wenwen Song; Cunxiang Wu (Crop Journal)
Dense cropping increases crop yield but intensifies resource competition, which reduces single plant yield and limits potential yield growth. Optimizing canopy spacing could enhance resource utilization, support crop morphological development and increase yield. Here, a three-year study was performed to verify the feasibility of adjusting row spacing to further enhance yield in densely planted soybeans. Of three row-spacing configurations (40–40, 20–40, and 20–60 cm) and two planting densities (normal 180,000 plants ha−1 and high 270,000 plants ha−1). The differences in canopy structure, plant morphological development, photosynthetic capacity and their impact on yield were analyzed. Row spacing configurations have a significant effect on canopy transmittance (CT). The 20–60 cm row spacing configuration increased CT and creates a favorable canopy light environment, in which plant height is reduced, while branching is promoted. This approach reduces plant competition, optimizes the developments of leaf area per plant, specific leaf area, leaf area development rate, leaf area duration and photosynthetic physiological indices (Fv/Fm, ETR, Pn). The significant increase of 11.9%–34.2% in canopy apparent photosynthesis (CAP) is attributed to the significant optimization of plant growth and photosynthetic physiology through CT, an important contributing factor to yield increases. The yield in the 20–60 cm treatment is 4.0% higher than in equidistant planting under normal planting density, but 5.9% under high density, primarily driven by CAP and pod number. These findings suggest that suitable row spacing configurations optimize the light environment for plants, promote source-sink transformation in soybeans, and further improve yield. In practice, a 20–60 cm row spacing configuration could be employed for high-density soybean planting to achieve a more substantial yield gain.